ChemInform Abstract: Single‐Electron Transmetalation in Organoboron Cross‐Coupling by Photoredox/Nickel Dual Catalysis. Issue 4 (January 2015) - Tellis, John C.; Primer, David N.; Molander, Gary A.
Abstract Application of an iridium photoredox catalyst IPC in combination with a nickel catalyst effects the cross‐coupling of potassium alkoxyalkyl‐ and benzyltrifluoroborates with various aryl bromides under exceptionally mild conditions (visible light, ambient temperature, no strong base).